PENERAPAN METODE ACTIVITY BASED COSTING UNTUK MENENTUKAN HARGA POKOK PRODUKSI - Satria, Hendy (Jurnal Benefita, 2017)
This study aims to determine the calculation of the cost of production by using Activity Based Costing in PD ADI ANUGRAH Tanjungpinang on both the company's products they are jerky cuttlefish dry fish jerky (lome), which was originally PD ADI ANUGRAH Tanjungpinang calculating the cost of production by using conventional methods. This research is descriptive quantitative research, data types and sources of data used are primary data and secondary data. Methods of data collection and data processing is done through observation, interviews with company leaders and employees as well as the study of literature in PD ADI ANUGRAH Tanjungpinang to obtain data. Activity Based Costing is a method used to obtain penhitungan cost of production is more accurate. Than generally based on the observation that PD ADI researchers reviewed Tanjungpinang ANUGRAH can use Activity Based Costing method for calculating the cost of production of their products in order to get an accurate cost of production.